RECONSTRUCTION OF ORBITAL FLOOR FRACTURES USING SILICONE BLOCK IMPLANT: Oral Presentation - Observational Study - Ophthalmologist - SYUKRIYAH SOFYAN (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : It has long been a controversial-both the materials for orbital floor reconstruction and the timing of surgery. Silicone block implant is affordable and readily available especially in developing countries. Due to its complications and the development of other materials, silicone block implant has rarely been used. This study aims to evaluate the outcomes of timing of surgery and the use of silicone block implant in orbital floor fractures reconstruction. Methods : We conducted a retrospective review of patients who had orbital floor fractures and undergone reconstruction surgery using silicone block implant in Cipto Mangunkusumo Hospital from January 2017 to December 2021. These patients then divided into three groups based on their surgery interval time. Outpatient notes, Computed Tomography (CT) reports, surgical admission notes, records and complications were recorded. Patients with follow-up less than three months were excluded. Results : Thirty-one patients were included (23 males, 8 females) with age 18-60 years old being dominant. Thirty (96.8%) patients had unilateral fractures, 23 patients (74.2%) came with impure fractures, and fractures mostly caused by traffic accidents (83.9%). Subconjunctival bleeding and eyelid abnormalities were found as the majority of ocular involvement. Symptoms with the greatest improvement were different between three groups based on surgery interval time. Besides, only one extruded implant was found. Conclusion : Silicone block implant provides good outcomes with minimal complications even after late surgical repair of orbital floor fractures.